THE IMPORTANCE OF INCREASE FINANCIAL LITERACY AMONG THE POPULATION (Marketing Journal, 2025)
Financial literacy plays a crucial role not only in economic development but also in personal growth. Personal development encompasses both socio -cultural aspects on one hand and physical -psychological development on the other. At the core of any developme nt lies financial status and financial literacy. This article analyzes the level of financial literacy among the population residing in different regions of the Republic of Uzbekistan, identifies existing shortcomings, and provides practical suggestions an d recommendations for improvement.
Keywords: financial literacy; standard of living of the population; finance; money; financial freedom; financial dependence; budget